2004
DOI: 10.1038/sj.ejhg.5201172
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol kinase deficiency: residual activity explained by reduced transcription and enzyme conformation

Abstract: Four unrelated patients with glyceroluria ranging from 7 to 170 mmol/l were studied. The activity of glycerol kinase (GK) in cultured fibroblasts was determined with a specific enzyme assay and with two indirect methods, that is, incorporation into macromolecules of [ 14 C] from [ 14 C]glycerol and its oxidation to [14 C]CO 2 . Exon amplification and RT-PCR were used to identify mutations. In patient 1, with low activity in all three assays, we identified a c.1194A4C (E398D) missense mutation. In patient 2 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
(31 reference statements)
1
9
1
Order By: Relevance
“…The mutation created a cryptic splice acceptor site, resulting in alternative splicing of the transcript with a small amount of correctly spliced GK mRNA. Likewise, we found that there were normal splicing in the splice-site mutations reported previous [4,5]. Sequencing the fragments, we found that the mutation caused a skipping of the whole exon17, leading a frame shift mutant of p. Val446Glufs*48.…”
Section: Analysis Of Gk Expression By Real-time Quantitative Pcrsupporting
confidence: 58%
See 2 more Smart Citations
“…The mutation created a cryptic splice acceptor site, resulting in alternative splicing of the transcript with a small amount of correctly spliced GK mRNA. Likewise, we found that there were normal splicing in the splice-site mutations reported previous [4,5]. Sequencing the fragments, we found that the mutation caused a skipping of the whole exon17, leading a frame shift mutant of p. Val446Glufs*48.…”
Section: Analysis Of Gk Expression By Real-time Quantitative Pcrsupporting
confidence: 58%
“…Zhang et al, found that aberrant mRNA generated by splice site mutations of the GK gene can be eliminated by NMD in the asymptomatic form of GKD [9]. In contrary, there was no NMD in our study, and reviewed the other split-site mutations previously reported, no NMD was found too [4,5]. Fourth, some studies demonstrated that glycerolutilization by the cells (especially, hepatocytes) is rate-limited by the membrane permeation step, rather than the GK step [13][14][15].…”
contrasting
confidence: 59%
See 1 more Smart Citation
“…1). In mammals, normal plasma glycerol levels range between 0.04 and 0.4 mM (18) with higher levels reported in cases subject to GK deficiency (32). Glycerol levels generally reflect the state of fat mobilization.…”
mentioning
confidence: 99%
“…GK deficiency (GKD) is an X-linked inborn error of metabolism that is characterized biochemically by hyperglycerolemia and glyceroluria and is due to mutations within or deletions of the GK gene on Xp21 (Rahib et al, 2007). Isolated GKD can occur in patients with or without symptoms, mainly due to disturbed energy homeostasis associated with hyperketotic hypoglycemia (Sjarif et al, 2004). The greater importance of glycerol as a gluconeogenetic substrate in children than in adults may explain the episodes in young patients with GKD, often elicited by catabolic stress .…”
Section: Glycero Kinase Deficiencymentioning
confidence: 99%